Additive effect ofÂ cow dung slurry andÂ cellulolytic bacterial inoculation onÂ humic fractions duringÂ composting ofÂ municipal solid waste - Mansi Rastogi; Meenakshi Nandal; Lata Nain (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The work aimed to investigate the effect of cow dung and cellulolytic bacteria on humic characteristics during municipal solid waste composting. Four Bacillus isolates (B. subtilis, B. tequilensis, B. venezuelans and B. amyloliquefaciens) sourced from dumpsite soil were formulated as consortium for the study. Methods Four treatments were considered with addition of bulking agents (ratio 1:7:6) to 15 kg MSW. Treatment Cs1 (control): only MSW, Cs2: MSWâ+âcellulolytic bacterial inoculum @ 5 ml (2âÃâ109 CFU mlâ1); Cs3âMSWâ+âcow dung slurry @ 1 kg (1:100 based on wet weight) and Cs4âMSWâ+âcellulolytic bacterial inoculum @ 5 ml (2âÃâ109 CFU mlâ1)â+âcow dung slurry @ 1 kg (diluted 1:100 based on wet weight). The analyses of humic acids were done by elemental analyzer, UV and Fourier transform infrared spectroscopy during 90 days of composting. Results MSW amended with consortia of effective microorganisms and cow dung slurry projected highest humification degree at 82.4% (Pâ<â0.01). Highest temperature (63 °C) was recorded in the treatment Cs4 during composting. The data corresponded to an increase in H/C ratio (0.9%) with a decrease in C/N (14.8%) and O/C ratio (0.5%). In addition, most stabilized values for E4/E6 ratio (4.1) and E2/E3 ratio (2.1) were observed in Cs4. The humification indices manifest positive regression values (F (4, 1)â=â0.007; Pâ<â0.01) and 99% significant model. Conclusion In the study, bio-augmentation (bacterial consortia and cow dung slurry) to MSW composting facilitates early maturity compared to other inoculated/uninoculated treatments. The result substantiates the effect of temperature on the humification rate of composting.